From eudaimonia to happiness. - Lauriola, Rosanna (Revista Espaço Acadêmico, 2021)
Among the common problems that, down through the ages, have puzzled humanity, from poets and philosophers to ordinary people, one can certainly include that of happiness. To wish each other happiness in several circumstances of life; to hear of persons who apparently have everything they thought they wanted and yet cannot say to be completely happy; to see persons who have everything we would think able to bring happiness meet, nonetheless, with all sort of problems – such as drug and alcohol – problems that the common sense would confine to the persons struggling with life; all of these are experiences and thoughts that each of us has had at least once. Ironically, it is possible that we, after having witness this paradox, nevertheless have never asked ourselves what happinnes is; or else, if we have, we have possibly experienced a feeling of uneasiness in trying to give an answer, that is, a not vague answer bordering in commonplaces.